Computer aided design and dynamic simulation of hydrostatic transmission systems - Polat, Erol. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1985., 1985)
In the present thesis, Computer Aided Design techniques are intended to be used for the design of Hydrostatic Transmission Systems and an user-friendly, interactive computer program package is developed for this purpose.Translational loads and cylinders are also considered so that the final program is an all purpose one. In addition, a mathematical model is derived for the dynamic behaviour of Hydrostatic Transmission Systems by taking the pressure compensation into consideration as well, and another interactive program is developed for simulation purposes. Each of the two programs may be used individually or together in an integrated manner. The User's Manuals are also offered to help the user. The CAD program is used for some example applications and computer simulations are carried out for different cases. The obtained results are presented.
Keywords: Hydrostatics.